CREATIVITY, INC : OVERCOMING THE UNSEEN FORCES THAT STAND IN THE WAY OF TRUE INSPIRATION - Catmull, Edwin E
In 1986, Ed Catmull co-founded Pixar, a modest start-up with an immodest goal: to make the first-ever computer animated movie. Nine years later, Pixar released Toy Story, which went on to revolutionize the industry, gross